Tolerância de plantas da caatinga com fenologia contrastante a seca - Lima, Lussarina Oliveira (2025)
The increase in the frequency and intensity of droughts in various regions of the planet has beenassociated with widespread plant mortality events, affecting biodiversity and the functioning ofecosystems. Hydraulic failure and lack of carbon are non-exclusive mechanisms that influenceplant mortality during drought. Hydraulic failure occurs when the plant loses its water transportcapacity (hydraulic conductance) due to embolism of the xylem vessels during soil drought.The relative importance of these mechanisms can differ between plants, and it is important toidentify them in order to project how climate change will affect the distribution and functioningof vegetation. There is currently no data on the critical thresholds for loss of xylem hydraulicconductance that cause hydraulic failure in tropical deciduous plants during drought. Inaddition, the effect of carbon depletion on plant functioning during drought is poorlyunderstood, which limits our current knowledge of how these two mortality mechanismsinteract. The aim of this study was to establish the tolerance limits of Caatinga species withcontrasting leaf phenology to drought, as well as to understand how a lack of carbon influencesthis response. We conducted a carbon stock manipulation experiment followed by a droughtexperiment to observe the effect of carbon depletion on gas exchange in the deciduous Caatingawoody species Bauhinia cheilantha. We also investigated the critical limits that cause hydraulicfailure in two Caatinga woody species, Cordia oncocalyx, an early deciduous species andCynophalla flexuosa, an evergreen species. We found that shaded B. cheilantha plants withdepleted starch reserves have lower gas exchange rates during drought than control plants. Theeffect of the shade treatment cannot be explained by differences in the photosyntheticcharacteristics of the leaf or structural differences in the xylem. Consequently, a stomataloptimization model based solely on xylem hydraulics cannot simulate the effect of shadetreatment on plant gas exchange during drought. In the drought experiments with the speciesC. oncocalyx and C. flexuosa we demonstrated the differences in how species of contrastingphenologies in the Caatinga respond to drought. The deciduous species responded more quicklyto drought than the evergreen species, showing higher rates of leaf loss and greater sensitivityof growth and gas exchange to drought. On the other hand, the deciduous species also showeda greater capacity to recover from drought than the evergreen species, so that no individual ofthe deciduous species died during the experiment. We found no evidence of a critical thresholdof Percentage Conductivity Loss (PPC) that causes sudden mortality due to hydraulic failure inany of the species. However, the evergreen species showed higher mortality rates when it wasexposed to a PPC > 99 % for several days, corroborating the hypothesis of mortality due tochronic stress. This work fills an important gap related to the effect of reduced carbon reserveson gas exchange and the critical threshold that causes hydraulic failure in tropical woody plantspecies from a semi-arid climate with different leaf phenologies. These results can be used toimprove vegetation models that represent hydraulic processes and carbohydrate dynamics inplants and their consequences for plant functioning. In this way, this thesis will contribute toimproving our ability to project the functioning and distribution of Caatinga vegetation inresponse to climate change.